INNOVATION STIMULATES THE FORMATION OF A SYNERGISTIC "EFFECT" IN THE ENTERPRISE (American Journal of Interdisciplinary Research and Development, 2022)
In this paper we describe the formation of synergistic "effects" soputstvuyushy to the economic effect due to the introduction to the activities of enterprises (for example, catering services and products catering), innovative techniques and technologies.